Satisfaction with childbirth services provided in public health facilities: results from a cross- sectional survey among postnatal women in Chhattisgarh, India - Paridhi Jha; Margareta Larsson; Kyllike Christensson; Agneta Skoog Svanberg (Taylor & Francis Group, 2017)
Background: A woman's satisfaction with childbirth services can have a significant impact on her mental health and ability to bond with her neonate. Knowing postnatal women's opinions and satisfaction with services makes the services more women-friendly. Indian women's satisfaction with childbirth services has been explored qualitatively, or by using non-standard local questionnaires, but scientific data gathered with standardised questionnaires are extremely limited. Objective: To measure postnatal Indian women's satisfaction with childbirth services at selected public health facilities in Chhattisgarh, India. Methods: Cross-sectional survey using consecutive sampling (n = 1004) was conducted from March to May 2015. Hindi-translated and validated versions of the Scale for Measuring Maternal Satisfaction for Vaginal Births (VB) and Caesarean Births (CB) were used for data collection. Results: Although most of the women (VB 68.7%; CB 79.2%) were satisfied with the overall childbirth services received, those who had VB were least satisfied with the processes around meeting their neonates (mean subscale score 1.8, SD 1.3), while women having CB were least satisfied with postpartum care received (mean subscale score 2.7, SD 1.2). Regression analyses revealed that among women having VB, interacting with care providers, being able to maintain privacy, and being free from fear of childbirth had a positive influence on overall satisfaction with the childbirth. Among women having CB, earning their own salary and having a positive perception of self-health had associations with overall birth satisfaction. Conclusions: Improving interpersonal interaction with nurse-midwives, and ensuring privacy during childbirth and hospital stay, are recommended first steps to improve women's childbirth satisfaction, until the supply gap is eliminated.